Recovery of p-GaN surface damage induced by dry etching for the formation of p-type Ohmic contact. (10th April 2019) - He, Junlei; Zhong, Yaozong; Zhou, Yu; Guo, Xiaolu; Huang, Yingnan; Liu, Jianxun; Feng, Meixin; Sun, Qian; Ikeda, Masao; Yang, Hui
Abstract: P-type Ohmic contact on the dry-etched p-GaN surface is highly desired for various device applications with the p-GaN buried underneath by an epitaxial layer or a dielectric layer. However, GaN dry etching process usually induces surface damage and inevitably degrades the p-type Ohmic contact performance. In this work, p-type Ohmic contact with a low specific resistivity has been successfully realized on a dry-etched p-GaN surface by using a wet chemical etching combined with a thermal treatment in NH3 /N2 ambient. Furthermore, the recovery mechanism of the p-GaN surface damage was studied through an in-depth surface characterization by atomic force microscopy and X-ray photoelectron spectroscopy.